Parasitic helminths in Boana pulchella (Duméril & Bibron, 1841) (Anura: Hylidae) and their relation with host diet, body size, and habitat - Silveira, Emily C. (2022)
We analyzed the diet and helminthological fauna of the frog Boana pulchella from the extreme south of Brazil. A total of 100 males were collected from two wetland areas in the state of Rio Grande do Sul: Ilha dos Marinheiros (n = 50) in the Rio Grande municipality, and the UFPel/ Embrapa (n = 50) in the Capão do Leão municipality. Boana pulchella food items and helminths found in different organs were identified and quantified. We analyzed the relationship between helminth assemblage and host diet, body size, and sampling sites. Boana pulchella presented a generalist diet, composed mainly of terrestrial insects, with diet richness higher at Ilha dos Marinheiros. Helminth fauna was composed of Nematoda, Cestoda, Digenea, and Acanthocephala, with no difference in helminth richness and abundance between sampling sites. However, the abundance of helminths presented a significant correlation with the volume of items found in the gastrointestinal contents of the anurans from UFPel/Embrapa-CL. Although for some helminth taxa there were significant differences in prevalence and mean intensity of infection among host size classes, the GLM (generalized linear model) between helminth abundance and anuran SVL (snout-vent length) was not significant. Oxyascaris oxyascaris, Cosmocercinae gen. spp., Ochoterenella sp., Diplostomidae gen. spp., Pseudoacanthocephalus sp., and Centrorhynchus sp. were the main taxa constituting the helminth assemblage associated to B. pulchella males at the sampling sites. The occurrence of helminths at larval and adult stages suggests that B. pulchella may occupy different trophic levels in the biological cycles of those helminths. This helminth parasitic fauna associated with B. pulchella is mainly composed of taxa with heteroxenous cycles involving several intermediate and paratenic hosts, which agrees with the observations of a typical generalist anuran diet in this species.